Analisis Kebutuhan Dokter Spesialis di Provinsi Jawa Timur Tahun 2020–2030 dengan Menerapkan Aplikasi Spectrum - Istianatul Ula; Rifanda Bachraini Firdaus (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
Human resources in the health sector need to be improved on both the aspects of quality and quantity. This is important for development planning. According to BPS in 2017 the population of East Java was 39,292,972 people, while in 2018 there were 39,500,851 people. Data from SISDMK revealed that there were 1,821specialist doctors in 2017 and 2,531 in 2018. This qualitative research was aimed at understanding and exploring deeply the secondary data obtained from the 2017–2018 SISDMK. The data was analyzed using Spectrum Software for population projection and human resource health needs. The results showed that the population projection of East Java kept increasing. In 2020 it will reach 39,886,288 people, and in 2030 there will be as many as 42,329,015 people. The projection of the number of specialist doctor needs in East Java in 2020 is 4,387, which will keep increasing to 5,079 in 2030. The ratio of specialist doctors in 2020 will be 36.26 per 100,000 population, and in 2030 it will be 35.27 per 100,000.